Perspectiva da homosexualidade: autodidentificação e vivências nas relações familiares de universitários - Andrade, Ana Carolina Netto (2023)
The debate around issues involving sexuality and gender has been gaining more and more space in recent decades, arising from cultural and historical changes and patterns that delimit social relations. The aim of this study was to understand the process of self-identification of university students' homosexuality and their experience in family relationships. This is a qualitative research in the phenomenological approach. The collaborators were young homosexual university students from 3 higher education courses at a university in the interior of São Paulo, invited through the snowball method or “snowball”, a sample that uses a chain of references. The interviews were scheduled, based on the acceptance of the collaborators and carried out through a dialogue guided by the following question: “tell me about your process of self-identification of your homosexuality and how it was to declare your affective orientation to your family members”. The interviews were recorded, transcribed in full, and later analyzed, beginning the understanding and interpretation of the questioned phenomenon.